2015
DOI: 10.1016/j.cis.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Speciation, stability, and coagulation mechanisms of hydroxyl aluminum clusters formed by PACl and alum: A critical review

Abstract: The physicochemical property of coagulant species plays a significant role in the coagulation process. Recent progress on speciation, stability, and coagulation mechanisms of the hydroxyl aluminum clusters formed by PACl and alum has been critically reviewed. The complicated nature on species formation, stability, and transformation of various hydrolyzed aluminum clusters formed by PACl and Alum are discussed. Based on the aspects of spontaneous hydrolysis, forced hydrolysis, and dual-hydrolysis models, the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(55 citation statements)
references
References 36 publications
1
52
0
2
Order By: Relevance
“…4, originates from the Al trimer (Al3). 5 The 27 Al spin-lattice (T1) and spin-spin relaxation times (T2) of all Al species were determined by the inversion recovery 40,41 and Carr-Purcell-Meiboom-Gill (i.e.,CPMG) procedures, [42][43][44] as shown in Table S4. This confirmed that T1 and T2 were much shorter than the FID acquisition time, and therefore, that 27 Al spin-lattice and spin-spin relaxation is almost complete ahead of the pulse radiation.…”
Section: Comparison Between the 27 Al Qnmr Analysis And The Ferron Asmentioning
confidence: 99%
See 1 more Smart Citation
“…4, originates from the Al trimer (Al3). 5 The 27 Al spin-lattice (T1) and spin-spin relaxation times (T2) of all Al species were determined by the inversion recovery 40,41 and Carr-Purcell-Meiboom-Gill (i.e.,CPMG) procedures, [42][43][44] as shown in Table S4. This confirmed that T1 and T2 were much shorter than the FID acquisition time, and therefore, that 27 Al spin-lattice and spin-spin relaxation is almost complete ahead of the pulse radiation.…”
Section: Comparison Between the 27 Al Qnmr Analysis And The Ferron Asmentioning
confidence: 99%
“…7 The Al 3+ ion exhibits extremely complicated hydrolysis behavior in aqueous solution; this behavior depends, among others, on the Al concentration, pH, and temperature. [4][5][6][7][8][9][10][11][12][13][14][15][16] Furthermore, the formation of various dissolved Al complexes, such as free [Al(H2O)6] 3+ (Al1), the Al dimer (Al2), the Al trimer (Al3), the Al tridecamer (Al13), and the Al triacontamer (Al30), and the precipitation of Al hydroxides have been confirmed. 4,5,10,[12][13][14][15][16] However, the hydrolysis behavior of the Al 3+ ion has not yet been quantified because destructive measurement methods were used for the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini terjadi karena dalam suasana basa, Al 3+ di dalam air terhidrolisis membentuk ion kompleks bermuatan positif (reaksi 4), ion ini memiliki kemampuan untuk menyerap permukaan partikel-partikel tersuspensi yang bermuatan negatif. 18,19,20 Ikatan rangkap pada zat warna akan menghasilkan suatu zatyang dibungkus dengan muatan negatif dari partikel-partikel tersuspensi. Zat ini kemudian diendapkan melalui proses koagulasi -flokulasi setelah penambahan tawas (Al 3+ ).…”
Section: Reaksiunclassified
“…Table 5 Application areas for speciation trace analysis [74] Element Application area for speciation analysis Aluminum Al Aggregates [75] Antimony Sb Redox forms and organoantimony compounds in the environment [76,77] Arsenic As Redox forms and organoarsenic compounds in the environment [77] Arsenic in food products [78] Forms of arsine in air [79] Cadmium Cd Cadmium in food products [80] Chromium Cr Redox forms of chromium, Cr(VI) in the environment [81,82] Lead Pb Forms of lead compounds in the environment [83] Mercury Hg Forms of mercury compounds in the environment [84][85][86] Selenium Se Inorganic and organometallic selenium compounds in the environment [87] Thallium Tl Thallium compounds in river water [88] Tellurium Te Tellurium compounds in the environment [89] Uranium U Forms of uranium compounds in seawater [90] Zinc Zn Forms of zinc compounds in the environment and food [91] The usual analytical procedure comprises filtration (to obtain the soluble and insoluble fractions), separation from the matrix and fractionation (e.g., by high-performance liquid chromatography (HPLC), size exclusion chromatography (SEC), gel permeation chromatography, anion/cation exchange chromatography, CZE, ultrafiltration, dialysis or gas chromatography in the case of volatile species). The isolated species are then determined by atomic absorption spectrometry, flame atomic absorption spectrometry, ICP-optical emission spectrometry, ICP-MS, MS, fluorimetry, atomic fluorescence spectrometry, UV-Vis, or electrochemical methods depending on the type of analyte [74].…”
Section: Tablementioning
confidence: 99%